THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP STYLE ON THE PERFORMANCE OF CONTENT DEVELOPMENT TEAMS AT THE DIGITAL EDUCATION STARTUP SANSGEN - Sabani, Rahmat; Mallongi, Syahrir (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to: (a) describe the transformational leadership style, work motivation, and employee performance; (b) examine the influence of transformational leadership on employee motivation; (c) analyze the effect of work motivation on employee performance; and (d) assess the indirect effect of transformational leadership on employee performance through work motivation. The research was conducted at the digital education startup Sansgen, involving all 74 employees using a total sampling technique. Data were analyzed using path analysis. The findings indicate that transformational leadership significantly influences work motivation (β = 0.587), and also has a direct effect on employee performance (β = 0.597). Furthermore, work motivation positively affects employee performance (β = 0.357), and acts as a mediating variable in the relationship between transformational leadership and performance, with an indirect effect of 0.201. These results suggest that transformational leadership plays a critical role in improving performance, both directly and indirectly, by enhancing employee motivation.